Quantifying the Effects of Altering Ambient Humidity on Ionic Composition of Vocal Fold Surface Fluid - Sivasankar, M. Preeti (2013)
OBJECTIVE: Vocal fold surface fluid (VFSF) is important in hydration and defense of underlying epithelial cells. The objective of this study was to quantify changes in the ionic composition of VFSF after altering the humidity of inhaled air. We tested the hypothesis that low humidity exposure would increase the concentration of VFSF sodium (Na(+)) and chloride (Cl(−)) ions but that high humidity exposure would decrease the concentration of VFSF Na(+) and Cl(−) ions as compared to the low humidity challenge. STUDY DESIGN: Prospective design. METHODS: Eighteen healthy adults participated in this study. VFSF was collected from each subject at baseline, and following exposure to low humidity and high humidity environments. VFSF Na(+) concentration was assessed using inductively-coupled plasma mass spectrometry. VFSF Cl(−) concentration was measured with indirect potentiometry. All analyses were completed by personnel blinded to the hypothesis being tested. RESULTS: The low humidity environment increased Na(+) concentration in the majority of the subjects. Data for changes in Cl(−) concentrations were variable. Overall the data did not reach statistical significance (p > 0.05). Subjective impressions suggested that VFSF collection was more difficult in low humidity as compared to the high humidity and baseline conditions. CONCLUSIONS: This study is the first attempt to measure the ionic concentration of VFSF. The results from the current study have important implications for future programmatic research quantifying the effects of pollutants and laryngopharyngeal reflux on VFSF composition, epithelial hydration, and vocal fold defense.